To find the solution with the lowest value, we need to solve each equation and compare the values of x.
1) x + 19 = -5
Subtract 19 from both sides:
x = -5 - 19
x = -24
2) x + 25 = 2
Subtract 25 from both sides:
x = 2 - 25
x = -23
3) x - 7 = 28
Add 7 to both sides:
x = 28 + 7
x = 35
4) x - 6 = -16
Add 6 to both sides:
x = -16 + 6
x = -10
Therefore, the equation with the solution of the lowest value is x = -24.
first question: Which of the following equations has the solution of the lowest value?
x+19=-5
x+25=2
x-7=28
x-6=-16
5 answers
second question: Which of the following equations has a different value of x than the others?
x+9/8=-7/4
x-78= -3/2
x-0.025=0.6
x+0.875=-1.5
x+9/8=-7/4
x-78= -3/2
x-0.025=0.6
x+0.875=-1.5
To determine which equation has a different value of x than the others, we need to solve each equation and compare the values of x.
1) x + 9/8 = -7/4
To eliminate fractions, we can multiply the entire equation by 8:
8(x + 9/8) = 8(-7/4)
8x + 9 = -14
Subtract 9 from both sides:
8x = -23
Divide both sides by 8:
x = -23/8
2) x - 78 = -3/2
Add 78 to both sides:
x = -3/2 + 78
x = 78 - 3/2
x = 156/2 - 3/2
x = 153/2
3) x - 0.025 = 0.6
Add 0.025 to both sides:
x = 0.6 + 0.025
x = 0.625
4) x + 0.875 = -1.5
Subtract 0.875 from both sides:
x = -1.5 - 0.875
x = -2.375
Therefore, the equation with a different value of x than the others is x = 0.625.
1) x + 9/8 = -7/4
To eliminate fractions, we can multiply the entire equation by 8:
8(x + 9/8) = 8(-7/4)
8x + 9 = -14
Subtract 9 from both sides:
8x = -23
Divide both sides by 8:
x = -23/8
2) x - 78 = -3/2
Add 78 to both sides:
x = -3/2 + 78
x = 78 - 3/2
x = 156/2 - 3/2
x = 153/2
3) x - 0.025 = 0.6
Add 0.025 to both sides:
x = 0.6 + 0.025
x = 0.625
4) x + 0.875 = -1.5
Subtract 0.875 from both sides:
x = -1.5 - 0.875
x = -2.375
Therefore, the equation with a different value of x than the others is x = 0.625.
If x/-5=2, then what is the value of x?
To find the value of x, we can multiply both sides of the equation by -5 since dividing by -5 is equivalent to multiplying by -1/5:
(x/-5) * -5 = 2 * -5
This simplifies to:
x = -10
Therefore, the value of x is -10.
(x/-5) * -5 = 2 * -5
This simplifies to:
x = -10
Therefore, the value of x is -10.